Causes, diagnosis, treatment and prognosis of root perforations - Alshamrani, Abdullah Saeed; Almusharraf, Abdullatif Yousif; Alshammari, Khalaf Awad; Ali, Eman Jawad Bo; Almutairi, Hamed Hamdan; Farrash, Fawaz Abdulhamid; Alghamdi, Hashem Saad; Alqahtani, Abdulrahman Ali; Alosaimi, Abdulaziz Ali (International Journal Of Community Medicine And Public Health, 2022)
A perforation is an artificial communication that occurs between the root canal system and the tissues enclosing a tooth. It can be made by the dentist during tooth preparation and passage into the root canal system, or it can happen naturally due to resorption or dental decay and cause connectivity between the root canal and periodontium. Both iatrogenic and non-iatrogenic factors can lead to a root being perforated. Most often, it happens at the coronal aspect of the tooth. Iatrogenic perforations can always be distinguished by the extensive bleeding that occurs after the wound. Serous discharge or fistula from the perforated site, sensitivity on percussing, isolated periodontal pocketing, and chronic gingivitis when the inflammation has reached the alveolus can all be signs of unresolved perforations. Cone beam computed tomography can be used to correctly identify and evaluate resorbing lesions and subsequent perforations. Successful perforation management involves adequately sealing the breach, using the right material, and closing the perforation in the right place as soon as feasible. Perforation management can be done in one of two ways: non-surgically or surgically. The prognosis of teeth with root perforations that have had endodontic treatment relies on a number of variables, including the amount of time that passed before the defect was sealed, the site of the perforation, the effectiveness of the perforation seal, and the size of the perforation. Due to the poor prognosis, teeth with suboptimal periodontal health or those with very wide perforations may be extracted.